Linguistic-cultural validation of a French version of the oral health assessment tool - Rapp Lucie; Vergnes Jean-Noel; Monsarrat Paul; Kémoun Philippe; Balardy Laurent; Lacoste-Ferré Marie-Hélène (BMC Oral Health)
Abstract Objectives The aim of this study is to conduct a linguistic-cultural validation for the French context, of the original Australian version of the Oral Health Assessment Tool (OHAT) scale. Methods The study design is a mixed retrospective-prospective psychometric and linguistic translation/validation/study of the Oral Health Assessment Tool. This validation involved two samples: a retrospective convenience sample of 1319 patients from the “Geriatric Frailty Clinic (GFC) for Assessment of Frailty and Prevention of Disability” and a prospective sample included 50 patients (34 from the long-term care unit and 16 from the neuro-locomotive follow-up care and rehabilitation unit). Results The face validity showed a clarity score for each item higher than 80%. The content validity was confirmed by a content validity index for items (I-CVI) score equal to or greater than 0.8 for each item and a content validity index for scales (S-CVI) of 0.91 for the entire tool. Internal consistency was considered good in the retrospective sample (Cronbach’s alpha value of 0.73) and excellent in the prospective sample (Cronbach’s alphas were 0.90 for each examiner). Inter-rater reliability was excellent for the total OHAT score (ICC = 0.98, 95% CI (0.97–0.99) at T0, and ICC = 0.99, 95% CI (0.99-1) at T1) and showed strong to almost perfect agreement (κ-values for single items varying from a minimum of 0.85 to 1) by items. Intra-rater reliabilities were considered substantial to excellent by items. Conclusions The French version of the OHAT is a reliable and valid tool for assessing the oral health of older people even with cognitive disorders.